Analiz techniki tjazeloatletov v ryvke pri odnokraftnom i dvuchkratnom pod'emach stangi s maksimal'noj ili blizkoj k maksimal'noj nagruzkoj - Poletaev, P.; Campos, J.; Cuesta, A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The purpose of the research was, on the one hand, to study the kinematical patterns that Spanish elite weightlifters implemented in the 2003 European Junior Championships in Valencia (Spain) to get the best results, and, on the other hand, to analyze the influence of the maximum or near maximum training load on the individual technique pattern of Spanish weightlifters. The 3D photogrammetry technique was used in the research.